2008
DOI: 10.1167/iovs.08-1877
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Optical Coherence Tomography Findings in Various Subtypes of Neovascular Age-Related Macular Degeneration

Abstract: OCT and angiography provide complementary information regarding CNV lesions. Quantitative analysis of OCT images allows for an improved understanding of the anatomic characteristics of angiographically defined CNV lesion subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 19 publications
1
57
0
1
Order By: Relevance
“…Various investigators have reported that SHRM occurs on fluorescein angiograms of eyes with leakage activity, 10,11 but that it may also correlate with hemorrhage, lipid, or thick fibrin. 18 Recently, various studies have described the presence of SHRM in treatment-naive n-AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various investigators have reported that SHRM occurs on fluorescein angiograms of eyes with leakage activity, 10,11 but that it may also correlate with hemorrhage, lipid, or thick fibrin. 18 Recently, various studies have described the presence of SHRM in treatment-naive n-AMD.…”
Section: Discussionmentioning
confidence: 99%
“…7 Notably, the status of the ellipsoid zone (EZ) and the external limiting membrane (ELM) has been shown to correlate with functional outcomes following anti-VEGF treatment. 8,9 One recently identified OCT feature in n-AMD is areas of altered reflectivity (low and high) that obscure normal retinal anatomical features, and these changes were first attributed to neovascular components by Liakopoulos et al 10 and Giani iovs.arvojournals.org j ISSN: 1552-5783…”
mentioning
confidence: 99%
“…The introduction of indocyanine green (ICG) angiography has enabled better visualization of choroidal circulation, and thus, neovascular AMD has become recognized as a broad spectrum of diseases that includes distinctive subtypes such as polypoidal choroidal vasculopathy (PCV) and retinal angiomatous proliferation (RAP). Further advancements in spectral domain optical coherence tomography (SD-OCT) has facilitated cross-sectional imaging of the retina with adequate resolution, which has consequently improved our understanding of these AMD subtypes [3-5]. Detailed imaging of the choroidal cross-section has also been recently achieved through the use of the Heidelberg Spectralis TM SD-OCT device with enhanced depth imaging (EDI) [6].…”
Section: Introductionmentioning
confidence: 99%
“…We speculate that a sort of RPE hyperplasia subsequent to mCNV formation is very likely to explain the shape and morphology of mCNV that can resemble occult CNV, in which most of the RPE layer is intact and does not permit the growth of new vessels toward the neuroretina [6]. Moreover, most of the lesion complex was confined close to or within the RPE layer.…”
Section: Discussionmentioning
confidence: 99%
“…The tomographic aspects of choroidal neovascularization (CNV) secondary to age-related macular degeneration (AMD) have been amply described [5,6], but mCNV has been studied less by SD-OCT, although these forms are among the main causes of vision loss in developed countries, estimated to occur in 5-10% of patients with high myopia [7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%